The Use of Natural Zeolite as A Catalyst for Esterification Reaction Between Glycerol and Oleic Acid - Anggara Diaz Ramadhan; Nindya Carolina C.S; Nuryoto Nuryoto; Teguh Kurniawan (Reaktor, 2019)
Natural zeolite in Indonesia generally divided into 2 types, which are mordernite and clinoptilolite. As far the use of zeolites is very limited. This experiment tries to use both types of natural zeolites to find out its work. The purpose of this experiment is testing the performance of mordenite natural zeolite from Bayah-Indonesia and clinoptilolite from Lampung- Indonesia in the esterification reaction between glycerol and oleic acid integrated by several variable that affect the reaction. The experiment will be done by using three-neck rounded flask batch reactor. The result showed that modernite zeolite has a better performance compared to clinoptilolite zeolite. To get the oleic acid conversion of 70%, clinoptilolite zeolite needs 4% catalyst of glycerol weight and reactant ratio of 6:1 mole of glycerol/mole of oleic acid, Meanwhile the mordernite zeolite only needs 2% catalyst of glycerol weight with reactant ratio of 4:1 mole of glycerol/mole of oleic acid.Keywords: natural zeolite; glycerol; reaction; diffusion